Barongsai Cap Go Meh di Makassar sebuah Pemikiran Tentang Tari, Ritual, dan Identitas - Batari Oja Andini (Universitas Gadjah Mada, 2016)
This article is a discussion of identity through performance. This research focuses onBarongsai (Lion Dance) performance on the Cap go Meh (Chinese New Year) ritual parade.The chosen research location is Makassar City, South Sulawesi. This research focuses onBarongsai in ritual context, as a compulsory attribute in the Cap go Meh Ritual Parade. Infurther explanation, this article also discuss about identity that constructed by Barongsaigroups. In order to earn an understanding of those issues, I use anthropological approachwith the participant observation and interview method. This research is a new line of themacro picture of the Tionghoa phenomenon in Indonesia